Challenging the Status Quo: Khaled M. Abou El Fadl’s Perspectives on Islamic Legal Authority and the Restrictive Fatwa on Women’s Solo Travel - Faiz, Muhammad Fauzinudin; Rohmatulloh, Dawam Multazamy; Solikhudin, Muhammad (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This article discusses Khaled M. Abou El Fadl’s (El Fadl) views on Islamic legal authority and his critique of the fatwa prohibiting women from travelling alone without a maḥram (unmarriageable kin) issued by the Council for Scientific Research and Legal Opinions (CRLO), Saudi Arabia. This research employs a literature review method by analysing several fatwas issued by the CRLO and several of El Fadl’s works as primary sources. The research findings indicate that El Fadl strives to formulate an authoritative and progressive Islamic law. El Fadl criticises the CRLO’s authoritarian fatwa regarding the prohibition of women travelling alone without a maḥram using a hermeneutic framework. El Fadl emphasises that the reader must understand the message of the religious text by connecting the text at the time of its revelation with the current text, considering the text’s competence, meaning determination, and representation. According to El Fadl, the hadith text used as a basis by the CRLO is no longer relevant in the current context because of the sense of security can be overcome on which the fatwa is based. The author argues that El Fadl’s views belong to progressive Muslim thinking. This article is expected to contribute to the discourse on openness and inclusivity in Islam.